Teknik Dispute Kognitif Terhadap Kecanduan Game Online Siswa - Syahran, Ridwan; Munifah, Munifah; Felayati Silalahi, Micha; Hasan, Hasan; Khalifah Usman, Nurul (Universitas PGRI Kanjuruhan Malang, 2025)
This study aims to test that students' online game addiction has decreased before and after being given group guidance with the cognitive dispute technique. The research sample amounted to 8 students based on purposive sampling technique. Collecting research data using online game addiction scale. The research data were analyzed using descriptive and inferential methods with the Wilcoxon Sign Rank Test formula. The results of descriptive analysis showed that before the provision of group guidance cognitive dispute techniques there were 4 students with high online game addiction classification and 4 students with moderate online game addiction classification. After being given group guidance on cognitive dispute techniques, there were 7 students with low online game addiction classification and 1 student with very low online game addiction classification. The results of inferential analysis show that the significance value is (Z=-2.524; p<0.05) with an average value of pretest (M=69.00; SD=9.710) and posttest (M=40.25; SD=8.242). The findings of this study indicate that students' online game addiction decreased significantly before and after being given group guidance with cognitive dispute techniques.